An Insight into the Challenges to Welfare of Small Ruminants in India and their Mitigation Strategies (Indian Journal of Animal Production and Management, 2024)
Small ruminants play a significant role in  economy of India, contributing to the production of  meat, milk, fibre, and skins. The rearing of these  small ruminants serves as a crucial source of  income and employment for a substantial portion of  the population, with the majority being comprised of  impoverished and small-scale farmers. Studies  addressing the challenges affecting the welfare of  small ruminants have been relatively scarce.  Additionally, research on strategies aimed at  mitigating the adverse effects of environmental  factors and management practices on small  ruminant welfare has been limited. This review aims  to discuss the challenges that impact the welfare of  small ruminants across various farming systems.  These challenges include extreme climatic conditions and seasonal fluctuations, inadequate  space and premises layout, microclimate control,  health problems and many more. Different  mitigation strategies are highlighted that can be  adopted for improving small ruminant welfare under  different production systems.
Keywords: challenges; climatic conditions; mitigation strategies; small ruminants; welfare